Pengaruh Profesionalisme, Kompetensi, dan Pengalaman Kerja Terhadap Kualitas Laporan Keuangan Badan Usaha Milik Desa di Kecamatan Sawan - Oky Novia; Edy Sujana (Universitas Pendidikan Ganesha, 2021)
This study aims to see the influence professionalism, competence, and work experience of the financial statement of Vilage-owned Enterprises in Sawan Subdistrict. The population of this research is all employees who work in Vilage-owned Enterprises Sawan Subdistrict totaling 137 people, the sample technique used is purposive sampling. The number of samples in this study were 39 respondents. The data analysis technique in this research is quantitative using multiple linear regression analysis which is processed with the help of SPSS 20 for Windows. The results of the study indicate that 1) professionalism had a positive and significant effect toward the quality of financial statement,(2) competence had a positive and significant effect toward the quality of financial statement, and (3) work experience had a positive and significant effect toward the quality of financial statement.Keywords: competence, professionalism, quality of financial statement, work experience